Refractory liver dysfunction was remarkably improved with chelating agents of Wilson's disease, in a patient with systemic lupus erythematosus-like syndrome after a parvovirus B19 infection. (2nd January 2021) - Nameki, Shinichiro; Maeda, Yuichi; Shibahara, Takayuki; Fukui, Jun; Shimizu, Takeshi; Bessho, Kazuhiko; Fujiwara, Hiroshi
Abstract: Parvovirus B19 infection has been reported to be associated with systemic lupus erythematosus (SLE). Liver dysfunction is frequently observed in SLE patients. However, liver dysfunction caused by an aberrant copper metabolism is rarely seen in patients with parvovirus B19 infection. We report a rare case of SLE-like and Wilson's disease (WD) mimicking symptoms that were simultaneously triggered by parvovirus B19 infection. A 29-year-old man was admitted to our hospital with high-grade fever, arthralgia, and oral ulcers following a parvovirus B19 infection. Laboratory tests showed elevated transaminase levels, proteinuria, anti-double-stranded DNA antibody, high levels of serum ferritin, and leukocytopenia. He was suspected of having SLE with haemophagocytosis and was treated with high doses of prednisolone. Subsequently, the patient's arthritis symptoms improved and the proteinuria improved. Immunosuppressive therapies improved most of his symptoms except for the high titre of transaminases were alleviated. Laboratory findings indicated low serum levels of ceruloplasmin and copper along with elevated levels of 24-hour urinary copper. Liver biopsy detected copper in hepatocytes. Although the hepatic copper content was relatively low in this case, the dysregulation of copper metabolism was considered to be a main cause of his elevated levels of liver enzymes. Therefore, we started treatment with chelating agents used in WD treatment. At the 2-month follow-up, the liver dysfunction had significantly improved. Our case suggests that in patients with refractory liver dysfunction due to unknown reasons, it is necessary to exclude the possibility that an abnormal copper metabolism had caused an increase in the levels of liver enzymes.